EFEKTIVITAS MEKANISME GUGATAN SEDERHANA DALAM PENYELESAIAN SENGKETA PERDATA DI INDONESIA DAN BELANDA: The Effectiveness of the Small Claims Mechanism in Resolving Civil Disputes in Indonesia and the Netherlands - Hatrik Sadewa Kadhasna Putra; Gandes Candra Kirana (Jurnal Hukum PRIORIS, 2025)
Civil justice systems in various countries face challenges in providing fast and affordable access to justice. The small claims procedure emerges as a solution to resolve low-value civil disputes efficiently. This article compares the regulation of small claims procedures in Indonesia and the Netherlands. The problem formulation include the similarities and differences, as well as the strengths and weaknesses, of the small claims systems in both countries.  Using a normative juridical method and comparative law approach. The result show that Indonesia limits small claims to cases under IDR 500 million and to simple legal matters, while the Netherlands applies a more flexible system known as kort geding, which has no monetary threshold and allows judges to take a more active role. In conclusion, although both systems aim to expedite dispute resolution, each adopts a different approach based on its respective legal tradition. These findings serve as an evaluative basis for improving the small claims system in Indonesia.